Bioinspired Synthesis of Mesoporous Gold-silica Hybrid Microspheres as Recyclable Colloidal SERS Substrates. Issue 1 (December 2017) - Son, Ho; Kim, Kyeong; Lee, Jun; Kim, Trang; Jang, Jihui; Kim, Su; Yoon, Moung; Kim, Jin; Nam, Yoon
Abstract Noble metal nanostructures have been intensively investigated as active substrates for surface-enhanced Raman spectroscopy (SERS) from visible to near-IR wavelengths. However, metal nanoparticle-based SERS analysis in solutions is very challenging due to uncontrollable and irreproducible colloid aggregation. Here we report the templated synthesis of porous gold-silica hybrid microspheres and their application as reusable colloidal SERS substrates. Mesoporous polymer microspheres are synthesized and used as templates for the synthesis of non-aggregated gold nanoparticles, followed by polydopamine-mediated silicification to fabricate mesoporous gold-silica hybrid microspheres. The mesoporous hybrid particles detect crystal violet in the order of 10–8  M and provide the structural durability of the immobilized gold nanoparticles, allowing them to be recycled for repeated SERS analyses for analytes in a solution with the similar sensitivity. This work suggests that the mesoporous gold-silica hybrid microspheres are attractive SERS substrates in terms of reusability, sensitivity, and stability.